1974
DOI: 10.1136/gut.15.6.473
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of primary biliary cirrhosis: A survey of mortality in England and Wales

Abstract: SUMMARY Primary biliary cirrhosis is a rare disease in the general population. Estimates of its true incidence are difficult but since survival time is unaffected by treatment, mortality may reflect important regional and other variations. One hundred and sixty-five death certificates collected in England and Wales over the five-year period 1967-1971 were inspected and confirmed an overwhelming predilection for females. Deaths rose sharply at ages 50-54 in the latter with a peak of 4.1 million-' year-', with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 18 publications
3
20
0
4
Order By: Relevance
“…However, this increase was not statistically significant. Many previous studies have shown steadily increasing incidence numbers in the last few decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our results indicating stable incidence are in line with the two other studies, which also have reported the highest incidence numbers so far, also showing unchanged incidence [21,27].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…However, this increase was not statistically significant. Many previous studies have shown steadily increasing incidence numbers in the last few decades [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Our results indicating stable incidence are in line with the two other studies, which also have reported the highest incidence numbers so far, also showing unchanged incidence [21,27].…”
Section: Discussionsupporting
confidence: 95%
“…However, case finding methods seem to have improved since the first studies on the epidemiology of PBC were published [2][3][4][5][6][7][8]. These preliminary studies often relied on a single source for case identification and found the incidence of PBC to be between 0.6 and 13.7 new cases per million each year and prevalence to be between 23 and 128 cases per million [2][3][4][5][6][7][8][9]. Studies conducted more recently have shown markedly higher results, with an incidence of 0.7-49 cases per million a year and prevalence between 6.7 and 492 cases per million [1,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite its poor response to immunosuppressive treatment, PBC is often considered a typical organ-specific autoimmune disease, in view of its female preponderance, its immunophenotypical features of bile duct pathology and its hallmark immune-serological signatures [1,5,6]. The reported incidence and prevalence of PBC ranges from 0.7 to 49 and 6.7 to 402 per million, respectively [7][8][9][10][11][12][13][14]. Different ethnicity and geographical backgrounds are acknowledged to account for this epidemiological disparity [15].…”
Section: Primary Biliary Cirrhosismentioning
confidence: 99%
“…The first study on the epidemiology of PBC was performed in 1974 by Hamlyn and Sherlock [8], who examined 165 death certificates collected in England and Wales over the 5-year period from 1967 to 1971. This corresponds to a crude rate of 1.2 million per year for females or 0.6 million per year for both sexes [8]. The new era for studying the epidemiology of PBC began in 1990 with the lesson from Newcastle in the UK [9].…”
Section: Geoepidemiologymentioning
confidence: 99%